Analysis Of Environmental Carrying Capacity And Accompanying Capacity For Water Supply Ecosystem Services In Ternate City - Tidore, Faedly; H Tidore, Muh Faedly; Adriani, Adriani; Arif, Nurfadhilah; B, Sabaruddin (Jurnal Penelitian Kehutanan BONITA, 2025)
Environmental carrying capacity and environmental load capacity (D3TLH) are important instruments in spatial planning mandated by Law No. 32 of 2009 and Law No. 26 of 2007. This study aims to analyze the environmental carrying and loading capacity based on water provisioning ecosystem services in Ternate City. Although ecosystem services-based approaches have been widely implemented across various Indonesian regions, research specifically addressing Ternate City as a volcanic island area with distinctive geographical characteristics remains considerably limited. Furthermore, water carrying capacity data for Ternate City are insufficient, and comprehensive spatial mapping illustrating the distribution of water provisioning ecosystem service potential has yet to be developed. The method used is a supply-demand comparison approach using a 1" x 1" grid system (±30 m²) with the Simple Additive Weighting (SAW) method to calculate environmental service indices based on landform, vegetation, and land cover parameters. The results show that water provisioning environmental services in Ternate City are dominated by low potential class (very low-low) covering 71.06%, medium potential class 27.52%, and high potential class (high-very high) only 1.42% of the total area. Batang Dua and West Ternate sub-districts have the highest potential with high class percentages of 0.50% and 0.18%, respectively. Land covers contributing the most are Dry Land Forest (0.96%) and Lake (0.28%). The analysis shows that the environmental carrying capacity for water provision in Ternate City is classified as low, influenced by rainfall, groundwater storage capacity, and land use activities. Protection efforts for water provider base areas are needed for sustainable water availability in the future.